Dielectric and ferroelectric properties of 0.8PZT-0.2PCN ceramics under sintering conditions variation - Anurak Prasatkhetragarn (2018)
The influences of sintering conditions on electrical properties of the 0.8Pb(Zr1/2Ti1/2)O3-0.2Pb(Co1/3Nb2/3)O3ceramics have been investigated with sintering temperatures of 1175, 1200, 1225, and 1250 °C and dwell times for 2, 6, and 10 h. The crystal structure of dense specimens showed coexistence between tetragonal, rhombohedral and pseudo cubic phases in all sintering temperatures, while tetragonal-rich phase appeared with increasing dwell times. A maximum dielectric constant was observed at sintering condition of 1200 °C for 2 h, while the transition temperature slightly increased with increasing dwell time. All ceramics also showed diffused phase transition behaviors with a minimum diffusivity at sintering condition of 1200 °C for 2 h. In addition, the polarization-electric field (P-E) hysteresis loops of the ceramic systems also changed significantly with sintering conditions. Interestingly, the ferroelectric parameters; remnant polarization (Pr) and loop squareness (Rsq) tended to increase with increasing sintering temperatures and dwell times. © 2009 Elsevier B.V.